Problem of man in world view Shakarіm (Journal of Philosophy Culture and Political Science, 2018)
Sh. Kudaiberdiev began to take shape as a person at the end of the nineteenth century, came on the stage ofhistory in the early twentieth century, while in the steppe region were complex socio-political change, and that isone of the representatives of the Kazakh intelligentsia, which, together with native people went through all thehardships of the transition period and who was engaged in philosophical studies in the context of the historicalrealities. Shakarim Kudaiberdiev is intellectual, which, along with other thinkers, to deal with a man raised to acertain level of ethical, moral and conscience. Analyzing the set Shakarima fi ve famous questions that completelycover such phenomena as the nature of man, his life, the future, the measure of his life, we can conclude that itis a teaching anthropology at the Kazakh interpretation. And in the course of their research Shakarim studied theplace and role of man in the Kazakh philosophy.Key words: Shakarіm, world view, man, conscience, personality.